Pembuatan Standard Operating Procedure (SOP) Pengelolaan Arsip Dinas Kearsipan dan Perpustakaan Provinsi Sumatera Barat - Daini, Helmi; Marlini, Marlini (Program Studi Informasi, Perpustakaan, dan Kearsipan , Jurusan Bahasa dan Sastra Indonesia, 2017)
The purpose of this paper is to guide the implementation of archive management activities both archive management and dynamic archive management. Data were collected through observation, interview, and literature study. Data analysis was done by descriptive method. Based on the discussion, it can be concluded that the stages of making Standard Operating Procedure (SOP) of Archive Management in West Sumatera Provincial Office and Library are: a) to collect as much information as possible about the archive management process; B) conduct discussions to receive opinions and input from archivists; C) create a standard draft with the team; D) drill tests that have been made; E) if the SOP is deemed effective enough, then do the approval of the head of the field of coaching; F) using language that is easy to understand; G) identity creation; H) list supporting documents; I) list the date of creation and date of revision; And j) list the authorized officer.Keywords : Archive, Standard Operating Procedure.